2011
DOI: 10.1177/1941738111411698
|View full text |Cite
|
Sign up to set email alerts
|

Tattoo-Induced Skin “Burn” During Magnetic Resonance Imaging in a Professional Football Player

Abstract: The authors present the case of a professional football player with an immediate and sustained cutaneous reaction (“burn”) at the site of lower extremity tattoos that occurred during magnetic resonance imaging of the pelvis. The burn was attributed to an electromagnetic reaction due to the ferromagnetic metallic compounds found in tattoo pigments, especially iron oxide—a reaction that has the potential to distort the field of image. These compounds can theoretically create an electric current that increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 10 publications
2
31
0
1
Order By: Relevance
“…Inks used for tattooing contain filings of metals, which can theoretically create an electric current during magnetic resonance imagining that increases the local skin temperature enough to cause pain and skin burns. 19 Among the respondents with tattoos, most of them untruthfully believed that tattoos cannot interfere with the performance of certain diagnostic and therapeutic procedures including magnetic resonance imaging, surgeries, and diagnosis of melanoma and skin cancers. Regarding this latter question, as previously, a significantly higher knowledge is showed by the students from the Medical University of Gda nsk, as more than half of them answered this question correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Inks used for tattooing contain filings of metals, which can theoretically create an electric current during magnetic resonance imagining that increases the local skin temperature enough to cause pain and skin burns. 19 Among the respondents with tattoos, most of them untruthfully believed that tattoos cannot interfere with the performance of certain diagnostic and therapeutic procedures including magnetic resonance imaging, surgeries, and diagnosis of melanoma and skin cancers. Regarding this latter question, as previously, a significantly higher knowledge is showed by the students from the Medical University of Gda nsk, as more than half of them answered this question correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, occasional case reports were published since the introduction of MRI in clinical routine about 25 years ago, but the literature is rather scarce and systematic and detailed studies are lacking . The relative paucity of reports indicates that adverse events related to MRI and tattoos are unusual or innocent, nevertheless, in one study observed in 1.5% having cosmetic tattoos .…”
Section: Introductionmentioning
confidence: 99%
“…6 There is a report of a tattoo-induced skin burn. 7 Additionally, there are some reports of bite blocks, spiral endotracheal tubes, and even cerebral artery clips either completely removed or displaced in the MRI room under general anesthesia. 8,9 Due to these reports, we undertook a risk mitigation strategy.…”
Section: Discussionmentioning
confidence: 99%